Ludwig Wittgenstein in Queer Film History - Witczak, Krzysztof (Sensus Historiae, 2023)
The article deals with the cinematic representation of the figure of Austrian philosopher Ludwig Wittgenstein in selected biographical works. The author analyzes the way of portraying the thinker as a popular figure, which is often the subject of films due to the search for hitherto untouched elements of personal history. One example of found history is Filip Radziszewski’s queer interpretation of an episode from the philosopher’s life in the film MS101.